2012
DOI: 10.1159/000342202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Age, Emergency Department Length of Stay and Hospital Admission Rate in Emergency Department Patients Aged ≥70 Years

Abstract: Background: Interdisciplinary emergency departments (EDs) are confronted with trauma and nontrauma patients of any age group. Length of stay (LOS) and admission rates reflect both disease complexity and severity. Objective: To evaluate LOS and admission rates in different age groups according to traumatic and nontraumatic etiologies. Patients and Methods: During May 2011 a total of 4,653 adult patients (defined as ≥18 years old) seen in the ED of our municipal hospital were evaluated for their primary problem,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
4
34
2
6
Order By: Relevance
“…In contrast, another found that frequent users had similar acuity and longer LOS 24. Among studies of the general patient population, a minority (three of nine) found that females had longer LOS;4 14 22 one other obtained this finding in univariate but not multivariate analyses,10 and the rest found no significant difference 7 11 17 26 39. Likewise, none of the studies of condition-specific populations reported a significant effect for sex in multivariate analysis.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, another found that frequent users had similar acuity and longer LOS 24. Among studies of the general patient population, a minority (three of nine) found that females had longer LOS;4 14 22 one other obtained this finding in univariate but not multivariate analyses,10 and the rest found no significant difference 7 11 17 26 39. Likewise, none of the studies of condition-specific populations reported a significant effect for sex in multivariate analysis.…”
Section: Resultsmentioning
confidence: 91%
“…However, three studies that analysed admitted and non-admitted patients separately found that only in the latter group did older patients stay longer;6 17 20 age effects were also detected in two studies of non-admitted patients10 19 but only one of admitted patients 26. Studies of condition-specific subpopulations tended not to show age effects (only one38 of nine studies 8 12 13 16 27 30 31 36 38) except among trauma patients (two of two studies) 7 25. Within the population of older adults (usually defined as 65+years), one study found an age gradient21 while two others did not 18 26…”
Section: Resultsmentioning
confidence: 97%
“…Diese Faktoren tragen dazu bei, dass im Gegensatz zu jüngeren Patienten die Verweildauer geriatrischer Patienten in der Notaufnahme häufig deutlich länger ist [19,20].…”
unclassified
“…Biber et al (2013) found a correlation between age and length of stay, with elderly trauma patients experiencing statistically longer lengths of stay. Lin et al (2012) used data mining techniques to examine the triage data of a major hospital and concluded that length of stay and the triage category are key parameters in determining emergency department costs.…”
Section: Literature Reviewmentioning
confidence: 90%